Effects of prebiotics, probiotics and synbiotics on serum creatinine in non-dialysis patients: a meta-analysis of randomized controlled trials. Issue 1 (31st December 2023) - Liu, Fenfen; Liu, Yang; Lv, Xueai; Lun, Hengzhong
Abstract: Objective: Serum creatinine level are influenced by many factors. Although accumulated data suggested that prebiotics, probiotics and synbiotics supplements could affect serum creatinine level, the results remained controversial. The aim of the present paper was to evaluate the effects of prebiotics, probiotics and synbiotics on serum creatinine in non-dialysis patients. Methods: PubMed, EMBASE (Excerpta Medica Database) and the Cochrane Library databases were searched for eligible randomized, controlled trials (RCTs) which were limited to English language studies until 30 September 2022. A random-effects model was performed to analyze the impact of pooled trials. Result: Twelve randomized, controlled trial studies were included in the meta-analysis. Prebiotics, probiotics or synbiotics supplementation did not significantly decrease the serum creatinine levels in non-dialysis patients compared to placebo [standardized mean difference (SMD) = 0.05; 95% confidence interval (CI): (−0.21, 0.31); p  = 0.72; I 2  = 61%]. Conclusion: The present meta-analysis indicated that supplementation with prebiotics, probiotics and synbiotics could not act as promising adjuvant therapies to decrease the serum creatinine levels in non-dialysis patients.